Before Ethereum. The Origin and Evolution of Blockchain Oracles - Giulio Caldarelli (IEEE Access, 2023)
Before the advent of alternative blockchains such as Ethereum, the future of decentralization was all in the hands of Bitcoin. Together with Nakamoto itself, early developers were trying to leverage Bitcoin’s potential to decentralize traditionally centralized applications. However, because Bitcoin was a decentralized machine, the available non-trustless oracles were considered unsuitable. Therefore, strategies had to be elaborated to solve the so-called “oracle problem” in the newborn scenario. By interviewing early developers and crawling early forums and repositories, this paper aims to retrace and reconstruct the chain of events and contributions that gave birth to oracles on Bitcoin. The evolution of early protocols, along with the difficulties encountered in their development, are also outlined. Analyzing technical and social barriers to building oracles on Bitcoin, the transition to Ethereum will also be discussed.